Evidence Supports Tradition: The in Vitro Effects of Roman Chamomile on Smooth Muscles - Sándor, Zsolt; Mottaghipisheh, Javad; Veres, Katalin; Hohmann, Judit; Bencsik, Tímea; Horváth, Attila; Kelemen, Dezső; Papp, Róbert; Barthó, Loránd; Csupor, Dezső (Frontiers in Pharmacology, 2018)
The dried flowers of Chamaemelum nobile (L.) All. have been used in traditional medicine for different conditions related to the spasm of the gastrointestinal system. However, there have been no experimental studies to support the smooth muscle relaxant effect of this plant. The aim of our research was to assess the effects of the hydroethanolic extract of Roman chamomile, its fractions, four of its flavonoids (apigenin, luteolin, hispidulin and eupafolin), and its essential oil on smooth muscles. The phytochemical compositions of the extract and its fractions were characterized and quantified by HPLC-DAD, the essential oil was characterized by GC and GC-MS. Neuronally mediated and smooth muscle effects were tested in isolated organ bath experiments on guinea pig, rat and human smooth muscle preparations. The crude herbal extract induced an immediate, moderate and transient contraction of guinea pig ileum via the activation of cholinergic neurons of the gut wall. Purinoceptor and serotonin receptor antagonists did not influence this effect. The more sustained relaxant effect of the extract, measured after pre-contraction of the preparations, was remarkable and was not affected by an adrenergic beta receptor antagonist. The smooth muscle-relaxant activity was found to be associated with the flavonoid content of the fractions. The essential oil showed only the relaxant effect, but no contracting activity. The smooth muscle-relaxant effect was also detected on rat gastrointestinal tissues, as well as on strip preparations of human small intestine. These results suggest that Roman chamomile extract has a direct and prolonged smooth muscle-relaxant effect on guinea pig ileum which is related to its flavonoid content. In some preparations, a transient stimulation of enteric cholinergic motoneurons was also detected. The essential oil also has a remarkable smooth muscle relaxant effect in this setting. Similar relaxant effects were also detected on other visceral preparations, including human jejunum. This is the first report on the activity of Roman chamomile on smooth muscles that may reassure the rationale of the traditional use of this plant in spasmodic gastrointestinal disorders.